2021
DOI: 10.3390/biomedicines9091154
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term SGLT2 Inhibitor Administration Does Not Alter Systemic Insulin Clearance in Type 2 Diabetes

Abstract: Background: Decreased insulin clearance could be a relatively upstream abnormality in obesity, metabolic syndrome, and nonalcoholic fatty liver disease. Previous studies have shown that sodium-glucose cotransporter 2 inhibitor (SGLT2i) increases insulin–C-peptide ratio, a marker of insulin clearance, and improves metabolic parameters. We evaluated the effects of the SGLT2i tofogliflozin on metabolic clearance rate of insulin (MCRI) with a hyperinsulinemic euglycemic clamp study, the gold standard for measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…20 Furthermore, no alterations in glucose uptake between the intervention group and the placebo group were identified. Comparable findings were reported by both Sato et al and Kern et al, showing the constancy of unaltered glucose uptake in skeletal muscle during a hyperinsulinemic-euglycemic clamp in humans 21 and mice. 22 Conversely, a recent study animal study reported decreased [ 18 F]FDG uptake in skeletal muscle within a diabetic mice model treated with dapagliflozin compared to controls.…”
Section: F I G U R E 7 Glucose Effectiveness (Ge) and Hepatic Insulin...supporting
confidence: 84%
See 2 more Smart Citations
“…20 Furthermore, no alterations in glucose uptake between the intervention group and the placebo group were identified. Comparable findings were reported by both Sato et al and Kern et al, showing the constancy of unaltered glucose uptake in skeletal muscle during a hyperinsulinemic-euglycemic clamp in humans 21 and mice. 22 Conversely, a recent study animal study reported decreased [ 18 F]FDG uptake in skeletal muscle within a diabetic mice model treated with dapagliflozin compared to controls.…”
Section: F I G U R E 7 Glucose Effectiveness (Ge) and Hepatic Insulin...supporting
confidence: 84%
“…Empagliflozin did not affect LPL activity 10.1 (CI95% 7.1-15.2) versus 12.6 (CI95% 8.9-18.0) μmol FFA/hour/g tissue, p = 0.10 (Figure 3E). In addition, empagliflozin did not change protein content of GLUT4 (30 ± 12 vs. 33 ± 13%, p = 0.30), HK-II (16)(17)(18)(19)(20)(21)(22)(23)(24)…”
Section: Lpl Activity and Protein Expression In Skeletal Musclementioning
confidence: 92%
See 1 more Smart Citation
“…All patients in our study were Japanese; therefore, our results contribute to everyday clinical work in the Asian population. A recent Japanese study indicated that the SGLT2i tofogliflozin did not change whole-body insulin clearance 30 . According to these results, SGLT2i treatment mainly increases hepatic insulin clearance, not whole-body insulin clearance.…”
Section: Discussionmentioning
confidence: 99%